Using nonexpert online reports to enhance expert knowledge about causes of death in dental offices reported in scientific publications: qualitative and quantitative content analysis and search engine analysis - Gaiser, Meike; Kirsch, Joachim; Mutzbauer, Till Sebastian (Journal of medical internet research, 2020)
Background: Fatalities rarely occur in dental offices. Implications for clinicians may be deduced from scientific publications and internet reports about deaths in dental offices. - Objective: Data involving deaths in dental facilities were analyzed using Google as well as the PubMed database. By comparing both sources, we examined how internet data may enhance knowledge about deaths in dental offices obtained from scientific medical publications, which causes of death are published online, and how associated life-threatening emergencies may be prevented. - Methods: To retrieve relevant information, we searched Google for country-specific incidents of death in dental practices using the following keywords: “death at the dentist,” “death in dental practice,” and “dying at the dentist.” For PubMed searches, the following keywords were used: “dentistry and mortality,” “death and dental treatment,” “dentistry and fatal outcome,” and “death and dentistry.” Deaths associated with dental treatment in a dental facility, attributable causes of death, and documented ages of the deceased were included in our analysis. Deaths occurring in maxillofacial surgery or pre-existing diseases involved in the death (eg, cancer and abscesses) were excluded. A total of 128 cases from online publications and 71 cases from PubMed publications that met the inclusion criteria were analyzed using chi-square statistics after exclusion of duplicates. - Results: The comparison between the fatalities from internet (n=117) and PubMed (n=71) publications revealed that more casualties affecting minors appeared online than in PubMed literature (online 68/117, 58.1%; PubMed 20/71, 28%; P <.001). In PubMed articles, 10 fatalities in patients older than 70 years of age were described, while online sources published 5 fatalities ( P =.02). Most deaths, both from internet publications and PubMed literature, could be assigned to the category anesthesia, medication, or sedation (online 80/117, 68.4%; PubMed 25/71, 35%; P <.001). Deaths assigned to the categories infection and cardiovascular system appeared more often in the PubMed literature ( infection : online 10/117, 8.5%; PubMed 15/71, 21%; P =.01; cardiovascular system : online 5/117, 4.3%; PubMed 15/71, 21%; P <.001). Furthermore, sedative drugs were involved in a larger proportion of fatal incidents listed online compared to in PubMed (online 41/117, 35.0%; PubMed: 14/71, 20%, P =.03). In the United States, more deaths occurred under sedation (44/96, 46%) compared to those in the other countries (Germany and Austria 1/17, 6%, P =.002; United Kingdom 1/14, 7%, P =.006). - Conclusions: Online and PubMed databases may increase awareness of life-threatening risks for patients during dental treatment. Negative aspects of anesthesia and sedation, as well as the number of deaths of young patients, were underestimated when reviewing PubMed literature only. Medical history of patients, medication dosages, and vital function monitoring are significant issues for practitioners. A high-impact finding from online reports was the underestimation of risks when performing sedation and even general anesthesia. Detailed knowledge of the definition and understanding of deep sedation and general anesthesia by dentists is of major concern. By avoiding potentially hazardous procedures, such as sedation-aided treatments performed solely by dentists, the risk of treatment-induced life-threatening emergencies may be reduced. - [J Med Internet Res 2020;22(4):e15304]
Gesehen am 20.05.2020